Current Systems in the Earth's Magnetosphere. (22nd April 2018) - Ganushkina, N. Yu.; Liemohn, M. W.; Dubyagin, S.
Abstract: The basic structure and dynamics of the primary electric current systems in the Earth's magnetosphere are presented and discussed. In geophysics, the word current is used to describe the flow of mass from one location to another, and its analog of electric current is a flow of charge from one place to another. An electric current is associated with a magnetic field, and they combine with the Earth's internally generated dipolar magnetic field to form the topology of the magnetosphere. The concept of an electric current is reviewed and compared with other approaches to investigate the physics of the magnetosphere. The implications of understanding magnetospheric current systems are discussed, including paths forward for new investigations with the robust set of observations being produced by the numerous scientific and commercial satellites orbiting Earth. Key Points: The basic structure and dynamics of the primary electric current systems in the Earth's magnetosphere is presented and reviewed The implications of understanding magnetospheric current systems are discussed, including paths forward for new investigations The concept of an electric current is reviewed and compared with other approaches to investigate the physics of the magnetosphere